Review Article on Vijaysar (Pterocarpus Marsupium Roxb): A Multidimensional Herb - Mahakal Nilesh; Gulhane Harshad (AYUSHDHARA, 2022)
Vijaysar is a traditional Indian medicinal plant commonly known as Asan or Bijaka, Indian kino, Malabar kino related to the family Fabacae (Leguminosae) and its commonly distributed in India and Srilanka. Vijaysar is one of the important medicinal plant describe in Indian system of medicine literature and has been used for various medicinal purposes. Heartwood and bark of Pterocarpus marsupium is used as a anti-diabetic remedies since thousands of years. The extract of this plant has been shown many pharmacological compound which are used in various diseases. Pterocarpus marsupium is clinically established herb as a potent anti-diabetic drug. Pterocarpus marsupium content many chemical constituents like pterostilbene, -epicatechin, pterosupin, marsupsin, etc. Several research study shows its efficacy in cataract and hypertriglyceridemia. The extract of this plant is also use as a cardiac tonic, anti-diarrheal, skin disorders, rejuvenator, and hepatoprotective. Ancient classical Ayurvedic literature have detailed description of Vijaysar (Pterocarpus marsupium). The aim of present review article is to study its pharmacological activity, cultivation, occurrence, distribution, botanical description, traditional medicinal uses, phytoconstituents, chemical constituents.